Articulação entre movimentos sociais, centrais sindicais e partidos políticos: a experiência da Frente Brasil Popular (2015-2018) - Coelho, Francisca Genilce Gomes Barbosa (2022)
This thesis addresses the Popular Brazil Front (FBP), an articulation originated in social movements, trade union centrals and political parties, conceived as a strategical project that resulted in an unprecedented organizational format. It has arisen in a context of political dispute since Brazil's 2013 protests, resulting from the deterioration experienced by political parties due to the criminalization promoted by a considerable portion of the Judiciary Power, Public Ministry, Federal Police and commercial media, leading to the collective subjects of the political struggle to strategically articulate themselves around it. Therefore, they have positioned themselves as protagonists in facing a scenario of a democracy attack and the dismantling of public policies via the withdrawn of civil, political and social rights. The methodological path has favored qualitative research and was carried out alongside with the reading of FBP documents and the bibliography on the Front theme, by studying primary and secondary sources, as well as observing the study object and its development; also opting for the use of different techniques, such as: exploratory interviews, semi-structured interviews via videoconference and audio recording with leaders from the FBP, due to the pandemic period. The research has met the specific objective of contextualizing the Brazilian reality at the moment when the articulation has arisen, and has researched and systematized its formation genesis, in the period from 2015 to 2018. Although each year the political situation is constituted by distinct contexts, the research reveals that the FBP has continuity, remains and reinvents itself in each new scenario, preserving itself as an articulation political subject, which demonstrates political maturity to sustain its dialogues and mobilization, while each of its composing members, which sustain it, keep their identities and autonomy. Thus, it can remain moving, given that throughout its duration, it is constituted by conditions that keep the tripod that compose the articulation standing (social movements, trade union centrals and political parties), confirming to be an organization with a lasting tendency, even though it must face the challenges of sharing power, seeking consensus in collective processes, not losing its identity and not becoming hegemonic of a single group